ANALYSIS OF THE STABILITY OF IDENTIFICATION METHOD OF DDOS-ATTACKS AT THE PHYSICAL LEVEL OF THE OSI NETWORK MODEL TO VARIOUS VARIATIONS OF LOADING ON THE CHANNEL - Roman Aidyn Mamedov; Vladimir Feokharovich Antonov (Современная наука и инновации, 2022)
The article presents an analysis of the developed method of identifying a distributed attack for denial of channel maintenance. Where the main aspect of the research is: the identification and removal of vulnerabilities from various ways of pseudo-legitimization of traffic by an attacker. Mathematical models of attack and its identification were developed, the application of which was realized through the Lazarus software development environment. The obtained results of computer modeling allowed to give an adequate estimation of the stability of the developed identification method and served as a tool for finding the solution to the problem identified. The results of the work are necessary for using this method in the system of dynamic expansion of the provider’s channel.